Acesso ao direito à saúde das crianças com síndrome congênita associada à infecção pelo vírus Zika - Araújo, Mariana de Oliveira (2021)
Congenital Syndrome associated with Zika virus infection (SCZ) is characterized by a series of manifestations in neonates who were exposed to the Zika virus during pregnancy, with neurological disorders, including congenital microcephaly, which require care and a multidisciplinary approach to ensure rehabilitation, treatment and the realization of the right to health for these children. Therefore, there is a need for the adoption of expanded and enforceable public policies that meet the different demands arising from SCZ and that assist in promoting health rights for the benefit of these children's citizenship, according to the Brazilian Federal Constitution. Thus, this study aimed to understand how access to the Right to Health of children with congenital syndrome associated with infection by the Zika virus has conformed, according to the dimensions of analysis of the political, economic, social, administrative and technical-clinical Right to Health; to analyze the Health Care and Social Protection strategies developed under the Unified Health System (SUS) and the Unified Social Assistance System (SUAS) to guarantee the right to health of children with congenital syndrome associated with Zika virus infection; describe the services used in the diagnosis and treatment and the activities developed to monitor children with congenital syndrome associated with infection by the Zika virus to guarantee the Right to Health; and discuss the facilities/ advances, difficulties/ limits, challenges and perspectives of access to the Right to Health for children with congenital syndrome associated with infection by the Zika virus. This is a critical-analytical study, from a Dialectic perspective, with the Municipal Health Secretariat as its setting, specifically the Epidemiological Surveillance, the Central Regulation Center and the Out-of-Home Treatment Sector; the Municipal Reference Center for Endemics; the Family Health Units and Basic Health Units; the Association of Fathers and Mothers of the Exceptional of Feira de Santana-BA. The study participants were made up of four groups: Group I (seven mothers / fathers or guardians); Group II (11 health professionals); Group III (nine SUS service managers); and Group IV (a local researcher on the Zika virus), totaling 29 participants. We used semi-structured interviews, systematic observation and document analysis as data collection techniques; the data were analyzed using the hermeneutic-dialectic method. The right to health of children with SCZ was characterized in this study from the dimensions of analysis of the Right to Health - political, economic, social, administrative and technical-clinical. The strategies carried out by health professionals in caring for children with SCZ and in social assistance services have sought to promote the realization of the right to health in its expanded conception. The Aconchego Project has contributed to the strengthening of individual, group and political empowerment of the families of children with SCZ The guarantee of the right to health of children with SCZ in the municipality of Feira de Santana-BA has been permeated by facilities / advances, difficulties / limits , challenges and perspectives. The facilities are related to the right to health being a legal guarantee and the existence of committed professionals, while some difficulties were mentioned and the demand for services was greater than the supply and the time and frequency for the early stimulation activities was lower. than necessary, among others. In addition, some challenges still permeate the realization of the right to health, such as the creation of a specific rehabilitation center to care for children with SCZ and the need for health and educational services prepared physically and professionally to receive them. Given these results, in the reality researched, negative and positive perspectives permeate the ‘horizon’ envisioned by the participants with regard to access to the right to health of children with SCZ. We realized that even with the legal apparatus of the right to health, there are difficulties for its practical effectiveness, which requires efforts and political will for the legal definitions to be effective. It is necessary the commitment of families, health professionals and managers, in order to transform practices in search of effective access to the right to health for children with SCZ.